E-Learning Menjadi Platform Pembelajaran Era Society 5.0 - I Wayan Titra Gunawijaya (Pramana: Jurnal Hasil Penelitian, 2021)
The industrial revolution 4.0 is a technological development that focuses on systems that are automatic or machine-based, to overcome human neglect in supporting life in the Japanese world looking at society 5.0 as an alternative to the 4.0 industrial revolution, the use of technology is also important in supporting learning activities in the world of education. then called the e-learning system. The approach used in this research is a qualitative approach by presenting the research results descriptively. The results of the study explain that E-learning as a conducive learning medium can be applied in the current 4.0 industrial revolution. Through the e-learning system it is easier for students to carry out the learning process, especially the teaching staff, both lecturers and teachers, only prepare learning material in an online system which is then uploaded to the e-learning platform. Learning models like this can actually make learning easier, especially from students, that is, students can easily make interactive activities with educators and students can easily access teaching materials that have been uploaded in e-learning.